The Enabling Materialities of the Charcoal Suit: A Study of the Politicizing Capacities of Hanna Saarikoski’s Performance C - Türkmen, Murat M. (Det Kgl. Bibliotek/Royal Danish Library, 2025)
This article focuses on the artist Hanna Saarikoski’s performance C and the charcoal suit
that becomes a co-performer in this work. The title of the performance, C, is a symbol for the
chemical element carbon, which relates to 1) the main material of the suit, carbonized willow
branches, and 2) the human ecological impact on the planet, often called the “carbon footprint”.
In this performance, Saarikoski walked through the heart of the city of Turku wearing a bulky
black suit, laden with more than one thousand charcoal sticks. I argue that performance C
addresses the human-induced environmental emergency by sensually politicizing it and that the
charcoal suit actively contributes to this politicizing process by generating sounds, interacting
with the surroundings, and thus enabling surprising encounters. In this article, approaching the
topic from the perspectives of new materialism, political performance art, and costume studies,
I will analyze the ways in which the charcoal suit works as a co-performer and thus contributes
to politicizing the human impact on the environment.